Neonatal Outcomes in Preeclampsia During Pregnancy - Putri, Noviyati Rahardjo; Septiana, Yesika Cahya; Larasati, Disa; Pinawati, Umi (GLOBAL HEALTH SCIENCE GROUP, 2024)
Preeclampsia is a pregnancy complication signified by the raise of blood pressure accompanied by proteinuria, maternal organ and uteroplacental dysfunction that occurs after 20 weeks of gestation. Preeclampsia is one of the main causes of maternal and neonatal morbidity and mortality worldwide. The effect of preeclampsia on neonatal outcomes is still a major concern, as preeclampsia contributes to poor neonatal outcomes. Objective: This study aims to analyze the impact of preeclampsia on neonatal outcomes in terms of weight, length, and APGAR score in the first minute. Method: The research used a retrospective approach with a case-control design. This research was conducted by collecting data at Dr. R. Soedjati Soemodiardjo Purwodadi General Hospital, Central Java, in 2021. The total sample was 204 pregnant women selected by simple random sampling, consisting of 102 pregnant women with preeclampsia and 102 without preeclampsia. The dependent variable was preeclampsia. The independent variables were neonatal outcomes regarding weight, length, and APGAR score in the first minute. Results: There is a significant effect of preeclampsia on body weight (p=0.011), body length (p<0.001), and APGAR score in the first minute (p=0.022) in neonates at Dr. R. Soedjati Soemodiardjo Purwodadi General Hospital in 2021. Conclusions: Neonates from mothers with preeclampsia tend to have lower weight, shorter length, and lower APGAR scores in the first minute compared to neonates from mothers without preeclampsia.